Exploring the current trends in curriculum design of entrepreneur education programmes through three case studies, in Cape Town, South Africa - Sexton, Emma (School of Education, 2017)
This comparative case study aims to identify the pedagogic approaches embedded in the design of a selection of entrepreneur education programmes. Three non-profit organisations based in the Western Cape, South Africa, were selected as case studies. While each organisation offers an entrepreneur education programme for previously disadvantaged individuals who are in the early stages of running a business, each programme is unique in terms of its target market industry sector, learning objectives and business outcomes, as well as in its curriculum design intended to enable particular objectives and outcomes to be optimally achieved by the learners (entrepreneurs). Activity Theory and Bernstein's Models of Pedagogy provide analytical frameworks for the study. Data was gathered from three semi-structured interviews carried out with the principal curriculum designer within each organisation, as well as written documents and websites. Engeström's extension of Activity Theory provided the conceptual tools for the first level of analysis of the case data, which identified tensions within and between the activity system elements of each curriculum. Further analysis was conducted utilising Bernstein's models of pedagogy, in order to better understand the key assumptions about learning and knowledge underpinning each of the curricula. Within each Activity System, significant tensions were identified between the Subjects, the Rules and Object; the Subjects, the Tools and the Object; and the Subjects, the Division of Labour, and the Object. Two approaches to pedagogy were evident within the three curricula, which aligned to Bernstein's competence and performance models of pedagogy. By drawing on the tensions identified through mapping the curriculum using Activity Theory, the thesis proposes that the two pedagogic models should be seen as a continuum and can be used to identify key questions to consider in the design of entrepreneur education curriculum, in order to ensure a well-informed curriculum aligned to adult learning theory and to the programme's learning objectives and business outcomes, and which addresses the unique context in terms of target market. Further research is necessary to understand whether the programmes which combine elements from various models of pedagogy do indeed enjoy better outcomes.